Refractive amblyopia among children in Ibadan: the need for amblyopia screening programmes (2015)
Background: The prevalence and burden of amblyopia in developing countries is probably underestimated, and little is known about the pattern of amblyopia in West Africa. Aim: To determine the relative frequency and types of amblyopia among children with refractive errors seen in the eye clinic of a tertiary hospital over a 2 year period. Methods: A cross-sectional study conducted at the eye clinic of the University College Hospital, Ibadan, Nigeria between January 2012 and December 2013. Case notes of children with refractive errors seen during this period were retrieved and information including socio-demographic data, presenting visual acuity and visual acuity with correction were recorded. Amblyopia was defined as best corrected visual acuity worse than 6/9 or a difference of >2 Snellen chart lines between both eyes in the absence of any ocular pathology that could explain the visual impairment. Results: A total of 250 eligible patients who had refractive errors were included in the study. Visual acuity was corrected to 6/9 or better in 224 (89.6%) children while 26(10.4%) of them had amblyopia. Among the 26 children with amblyopia, 21 (80.8%) children had amblyopia in both eyes and majority (65.4%) had isoamctropic amblyopia. Of the 47 amblyopic eyes, 36 (76.6%) eyes had moderate amblyopia while 11 (23.4%) eyes had severe amblyopia. Conclusion'. There is a high relative frequency of amblyopia in this study and we recommend preschool eye examinations for all children to ensure early detection and management of amblyopia, thereby reducing the burden of amblyopia in our populace.